2012
DOI: 10.1007/s00216-012-5782-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics reveals the deregulation of fatty acids metabolism in hepatocellular carcinoma and chronic liver diseases

Abstract: Patients with chronic liver diseases (CLD) including chronic hepatitis B and hepatic cirrhosis (CIR) are the major high-risk population of hepatocellular carcinoma (HCC). The differential diagnosis between CLD and HCC is a challenge. This work aims to study the related metabolic deregulations in HCC and CLD to promote the discovery of the differential metabolites for distinguishing the different liver diseases. Serum metabolic profiling analysis from patients with CLD and HCC was performed using a liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 49 publications
14
92
2
Order By: Relevance
“…Serum metabonomics showed that long-chain acylcarnitines accumulated, whereas free carnitine, medium and short-chain acylcarnitines decreased with the severity of the nonmalignant liver diseases, accompanied by the corresponding alterations of the enzyme activities. However, the magnitude of the changes was smaller in HCC than in hepatic cirrhosis, possibly due to the differences in energy metabolism in the tumor cells [33].…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 90%
“…Serum metabonomics showed that long-chain acylcarnitines accumulated, whereas free carnitine, medium and short-chain acylcarnitines decreased with the severity of the nonmalignant liver diseases, accompanied by the corresponding alterations of the enzyme activities. However, the magnitude of the changes was smaller in HCC than in hepatic cirrhosis, possibly due to the differences in energy metabolism in the tumor cells [33].…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 90%
“…This phonotype was evidenced by the following metabolic changes including the decrease in glucose, citrate, and glycerol 3-phosphate but the increase in lactic acid and pyruvate [64][65][66][67][68][69]. On the other hand, the common induction of beta-oxidation was exemplified by the elevation of 2-oxoglutarate and reduction of free fatty acids, carnitine and carnitine esters [61,64,66,68,[70][71][72][73]. This theme will be further explored in the next section.…”
Section: Updates In Liver Cancermentioning
confidence: 99%
“…Recently, metabolomics studies have been used in many fields, such as analyzing the physiologic response to toxicology , nutrition (Lee et al, 2010;Wong and Lodge 2012), and cancer (Lokhov et al, 2010;Sreekumar et al, 2009;Zhou et al, 2012), as well as diabetes and disease diagnosis . The blood metabolome is closely connected with all organs and tissues, and therefore it is convenient and informative for biomarker discovery.…”
Section: Application Of Metabolomics In Clinical Studiesmentioning
confidence: 99%